ANALISA RENCANA ANGGARAN BIAYA PROYEK PEMBANGUNAN PERUMAHAN CLUSTER TERAS ARUMAN TIPE 72/110 CIMAHI UTARA - Setiawati, Tia; -, Sutrisno (Jurnal Mahasiswa Terapan; Vol 1 No 4 (2025): Jurnal Mahasiswa Terapan, 2025)
One of the main processes in carrying out a project is knowing how much funds must be provided to build the building. On the other hand, there are many residents who are unaware of the budget required to build a single residental unit. The aim of study is to analyze the price of one unit of house type 72/110 in the Teras Aruman Cluster housing, to provide a reference price per-square meter for one unit of house type 72/110 in the Teras Aruman Cluster housing, and to determine the percentage of the planned construction progress by the 8th week. The method used in this research is quantitative. Data collection techniques include observation, interviews, and surveys. The total cost of the building is Rp. 454.412.851 ,-.  Compared to the total price from the developer, which is around Rp. 1,664,920,000, the total price per square meter is approximately Rp. 4.131.025,- . In the 8th week, the results showed that the Overall Total/Planned Weight was 3,05%, the Cumulative Progress was 3,06%, and the Total Cumulative Actual Progress was 16,24%.